2016
DOI: 10.1007/s11910-015-0603-8
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Neurologic Infections in Patients with Acquired Immunodeficiency Syndrome (AIDS)

Abstract: Infections of the central nervous system (CNS) in individuals with human immunodeficiency virus (HIV) remain a substantial cause of morbidity and mortality despite the introduction of highly active antiretroviral therapy (HAART) especially in the resource-limited regions of the world. Diagnosis of these infections may be challenging because findings on cerebrospinal fluid (CSF) analysis and brain imaging are nonspecific. While brain biopsy provides a definitive diagnosis, it is an invasive procedure associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 82 publications
3
13
0
6
Order By: Relevance
“…With regard to the aetiological diagnoses obtained by biopsy, in our study, most of them were CNS lymphoma, similarly to previous reports [2,[13][14][15][16][17][18][19][20]. Gildernberg et al found that CNS lymphoma was the primary cause of FBL, followed by PML [15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With regard to the aetiological diagnoses obtained by biopsy, in our study, most of them were CNS lymphoma, similarly to previous reports [2,[13][14][15][16][17][18][19][20]. Gildernberg et al found that CNS lymphoma was the primary cause of FBL, followed by PML [15].…”
Section: Discussionsupporting
confidence: 90%
“…When analysing global 30-and 90-day related mortality in our cohort, we observed that in the first 30 days, although the difference was not statistically significant, mortality was higher for those who were not biopsied, without any differences at 90 days. This could be related to a worse immunological status at diagnosis in the nonbiopsied group, and consequently the nonsignificant increase in mortality in the biopsied group could be explained by the diagnosis of other pathologies, such as primary CNS lymphoma and PML, which were described in other studies to have a lower survival rate than other causes of FBL [2,3,[14][15][16][17][19][20][21][22][23][24][25][26]. However, this analysis is limited by the small sample size of the biopsied patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequences of the exaggerated Th1-biased response are continual vicious inflammation, loss of BBB integrity, tissue damage and increased ICP, necessitating serial lumbar punctures [6], which paradoxically lead to continual increased ICP, a correlation that has previously been documented [6]; this Th1-dominant vicious cycle mimics the initial pretreatment Th2/Th17-biased vicious cycle of increased ICP (Fig. 1b).…”
Section: Consequences Of Irismentioning
confidence: 74%
“…Die Toxoplasma-Enzephalitis gehört nach wie vor trotz deutlicher Reduktion der Inzidenz mit 10 % zu den häufigsten AIDS definierenden Infektionen. Der Beginn ist meist subakut über mehrere Tage bis Wochen, seltener akut innerhalb eines Tages [5][6][7][8][9][10]. Fokale neurologische Ausfälle (z.…”
Section: Toxoplasma-enzephalitisunclassified
“…In den letzten 2 Jahrzehnten kam es infolge der verbesserten systemischen Therapie durch die Einführung der hochaktiven antiretroviralen Kombinationsthe-rapie (cART) zu einem weiteren drastischen Rückgang der opportunistischen Infektionen des ZNS [2,3]. Die UK Collaborative HIV Cohort (CHIC) Studie und andere Studien konnten nachweisen, dass die Inzidenz aller ZNS-Komplikationen inklusive der opportunistischen Infektionen von 13,1/1000 Patientenjahre im Jahr 1996/97 auf 1,0/1000 Patientenjahre in 2006/07 abnahm [4][5][6]. Die häufigsten opportunistischen Infektionen waren die progressive multifokale Leukoenzephalopathie (PML) (0,7/1000 Patientenjahre), die Toxoplasma-Enzephalitis (0,4/1000 Patientenjahre) gefolgt von der Kryptokokken-Meningitis (0,2/1000 Patientenjahre).…”
Section: Introductionunclassified